Answer:
x = -6/5
Explanation:
- 3(x + 2) = 2x
- You multiply -3 to the x and the 2 (which are in the parentheses)
- your equation will be -3x - 6 = 2x
- once you get that, you need to get the x's to one side and the constants (numbers) on the other side.
- you need to add the -3x so it becomes positive 3x. add the 3x to the right hand side where the 2x is.
- when you get here, it would look like -6 = 5x.
- now you have to divide by 5 to get x by its self. so divide 5 on both sides.
- once you do that you will get the answer as x = -6/5.
for the negatives, its just easy. u just have to make every thing negative if you are multiplying.